2022
DOI: 10.3390/bioengineering9080361
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Muscular Activity after Surgically Assisted Rapid Palatal Expansion: A Prospective Observational Study

Abstract: The study aims to investigate the modifications in the temporalis and the masseter activity in adult patients before and after SARPE (Surgically Assisted Rapid Palatal Expansion) by measuring electromyographic and electrokinesographic activity. 24 adult patients with unilateral posterior crossbite on the right side were selected from the Orthodontic Department of the University of Milan. Three electromyographic and electrokinesographic surface readings were taken respectively before surgery (T0) and 8 months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Adenotonsillary hypertrophy in children peaks in occurrence between the ages of 2 and 6 [43][44][45]. Within the same age range, the transverse section and volume of the upper airways are smaller, and the adenotonsillary volume-to-airway ratio is favorable to the former [46][47][48]. After six years, the ratio reverses, and the airway's transverse volume/section increases, but this is typically not accompanied by an increase in tonsillar or adenoid volume (the latter often tends to decline until normalization is achieved) [11,[49][50][51].…”
Section: Associations With Soft Tissues Neuromuscular Associations In...mentioning
confidence: 99%
“…Adenotonsillary hypertrophy in children peaks in occurrence between the ages of 2 and 6 [43][44][45]. Within the same age range, the transverse section and volume of the upper airways are smaller, and the adenotonsillary volume-to-airway ratio is favorable to the former [46][47][48]. After six years, the ratio reverses, and the airway's transverse volume/section increases, but this is typically not accompanied by an increase in tonsillar or adenoid volume (the latter often tends to decline until normalization is achieved) [11,[49][50][51].…”
Section: Associations With Soft Tissues Neuromuscular Associations In...mentioning
confidence: 99%
“…Expansion is one of the most common orthodontic treatments that create space to align teeth in the upper and lower arches [29][30][31]. Other therapeutic strategies exist to achieve arch space so that alignments and crowding can be resolved.…”
Section: The Expansion Problemmentioning
confidence: 99%
“…There is no evident aetiology of infraocclusions in the literature; however, it is possible to identify a specific histological profile. Histologic studies on primary molars in infraocclusion revealed degenerative changes in the pulp, such as fibrosis, calcifications, and areas of reduced cell activity in the periodontal ligament [ 21 , 22 ]. Ankylosis is histologically defined as the fusion of cementum/dentin to the bone in at least one area, resulting in the loss of the periodontal ligament space.…”
Section: Introductionmentioning
confidence: 99%